Polysomnographic characteristics and sleep‐disordered breathing in Schaaf‐Yang syndrome. Issue 11 (12th September 2020) - Powell, Weston T.; Schaaf, Christian P.; Rech, Megan E.; Wrede, Joanna
Abstract: Introduction: Schaaf‐Yang syndrome (SYS) is a genetic disorder caused by truncating variants in the MAGEL2 gene located in the maternally imprinted Prader‐Willi syndrome (PWS) region at 15q11‐13. The SYS phenotype shares features with PWS, a syndrome with known high incidence of sleep disorders. However, the spectrum of sleep‐disorders in SYS has not been described. Methods: We performed a retrospective analysis of polysomnograms from 22 patients in an international SYS cohort. Sleep characteristics for individuals with the common c.1996dupC variant ( n  = 10) were compared to other truncating variants ( n  = 11). Results: We collected 33 sleep study reports from 22 patients, ages 2 months – 18.5 years (mean 6.5 years). Mean sleep efficiency was 70.5% (range 45%–93%) with arousal index 14.1/h (1.2–45/h). The mean apnea‐hypopnea index (AHI) was 19.1/h (0.9–49/h) with mean obstructive AHI (oAHI) of 16.3/h (0.6–49/h). Mean central apnea index was 2.8/h (0–14/h). Mean oxygen desaturation index was 20.8/h (range 0–85/hr). Obstructive sleep apnea (OSA) was diagnosed in 81%, and 62% had moderate or severe OSA. Elevated central apnea index occurred in 9.5%. Comparison by genotype groups and age did not reveal any difference in OSA findings. Periodic limb movement index (PLMI) was elevated in 4/15 (26%). Conclusion: OSA is frequently identified on polysomnography in patients with SYS. The mean PLMI is elevated compared to normative data. Patients with SYS should have routine polysomnography screening due to high risk of sleep disorders.